Jemolo uditore di Buonaiuti Le postille alle lettere paoline - Bartola, Alberto; Fantappiè, Carlo 1953- (2021)
Our article aims to contextualize the «koinonía» meetings held in Rome by Ernesto Buonaiuti at the residence of the Guadagnini family from the end of 1919 to the first months of 1920. The meetings were devoted to reading and commenting the Pauline epistles. Arturo Carlo Jemolo, who attended those meetings, wrote down Buonaiuti’s explanations. Our article, which includes an unabridged publication of Jemolo’s annotations, analyses the historical and interpretative questions issued by Buonaiuti with regard to St. Paul’s letters.
Keywords: Arturo Carlo Jemolo; Ernesto Buonaiuti; Michael Hetzenauer; exegesis of St. Paul’s letters